Evaluation of oxidative stress according to the pattern of alcohol consumption and in alcoholic liver disease. - Adrián Flores-Sánchez; Abigail Hernández-Barragán; Daniela Colector-Sesatti; Andrea Garcia-Avalos; Moisés Martínez-Castillo; Marisela Hernández-Santillan; Jaqueline Córdova-Gallardo; José L. Pérez-Hernandez; Fátima Higuera-De la Tijera; Gabriela Gutiérrez-Reyes (Annals of Hepatology)
Introduction and Objectives: Alcohol and its metabolites induce damage in the liver, such as: activation of the immune response and oxidative stress. Objective: To evaluate the redox state through markers of oxidative stress in patterns of alcohol consumption and alcohol-related liver disease (ALD). Materials and Patients: A cross-sectional and multicenter study was conducted, with the inclusion of individuals displaying various patterns of alcohol consumption. Participants were categorized based on responses to questionnaires (AUDIT and DSM-IV), as well as an individualized survey, along with clinical and biochemical data. Six distinct groups were established: Risk (RI), Abuse (Ab), Alcoholism (OH), as well as ALD: alcohol liver cirrhosis (CiOH) and alcoholic hepatitis (HA), in addition to a control group (CT). Stress markers, including reduced glutathione (GSH) and oxidized glutathione (GSSG), were assessed in peripheral blood and we calculated GSH/GSSG ratio, lipid peroxidation via malondialdehyde formation, and protein oxidized by carbonylated protein were quantified. Statistical analysis was performed utilizing the Mann-Whitney U test, with statistical significance set at p<0.05. Results: The subjects were classified into RI (22), Ab (4), OH (28), CiOH (76), HA (16), and CT (100). The GSH was found to decrease significantly in the EHA groups vs CT. In contrast, GSSG increased in the RI, Ab, OH, and CiOH groups compared to CT, indicating that alcohol consumption favors an oxidizing state, confirmed by the negative GSH/GSSG ratio. Additionally, the GSH/GSSG ratio in the OH group showed a greater imbalance than in patients with EHA. On the other hand, protein oxidation increased in EHA, with high levels of carbonylated proteins observed in OH, CiOH, and HA compared to CT, Ab, and RI. Furthermore, lipoperoxidation measured by Malondialdehyde showed increased levels of OH and CiOH compared to the other study groups. Conclusions: Excessive alcohol consumption, with or without liver damage, promotes the oxidation of proteins and lipids. Additionally, alcohol favors the oxidized form of the main endogenous antioxidant, GSH. Therefore, it is necessary to control the redox balance through antioxidant treatment.